2015
DOI: 10.3762/bjnano.6.79
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of elasticity and damping in an α + β titanium alloy through atomic force acoustic microscopy

Abstract: SummaryThe distribution of elastic stiffness and damping of individual phases in an α + β titanium alloy (Ti-6Al-4V) measured by using atomic force acoustic microscopy (AFAM) is reported in the present study. The real and imaginary parts of the contact stiffness k * are obtained from the contact-resonance spectra and by using these two quantities, the maps of local elastic stiffness and the damping factor are derived. The evaluation of the data is based on the mass distribution of the cantilever with damped fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The deflections of the cantilever represent the morphological information, and the vibrations of the cantilever correspond to the acoustic signals. By employing a suitable mechanical model to describe the vibrations of the cantilever, the contact stiffness of the tip–sample interaction can be estimated [2728]. For one-phase homogeneous materials, the detected vibrations will remain relatively uniform, while for inhomogeneous materials, the vibrational amplitude depends on the elastic properties and the AFAM image will reflect the stiffness changes [29].…”
Section: Methodsmentioning
confidence: 99%
“…The deflections of the cantilever represent the morphological information, and the vibrations of the cantilever correspond to the acoustic signals. By employing a suitable mechanical model to describe the vibrations of the cantilever, the contact stiffness of the tip–sample interaction can be estimated [2728]. For one-phase homogeneous materials, the detected vibrations will remain relatively uniform, while for inhomogeneous materials, the vibrational amplitude depends on the elastic properties and the AFAM image will reflect the stiffness changes [29].…”
Section: Methodsmentioning
confidence: 99%
“…(2) can be eliminated provided that the measurements are carried out on a reference sample, for example, a single crystals or an amorphous material [44]. In case of polycrystalline materials, it has been successfully demonstrated that the matrix of polycrystalline materials can be used as a reference to determine the indentation modulus [36,38,39].…”
Section: Theory Of Afammentioning
confidence: 98%
“…In the past two decades, AFAM has been extensively used to study elastic properties of metallic glasses [33], polymers [34], clay minerals [35], nickelbase superalloys [36,37], titanium alloys [38,39], composite materials [40], cement paste [41], single crystals [42], thin films [43], Pyrex glasses [43], etc. Even though numerous studies have been reported on elastic properties of various materials, very few experimental data are available on the elastic properties of precipitates present in structural alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, physico-mechanical properties of intestinal cells were elucidated by force curve measurements by Eva Roblegg and co-workers [ 20 ]. The local elastic stiffness and damping of individual phases in a titanium alloys was measured by using atomic force acoustic microscopy (AFAM) and mapping of contact-resonance spectra [ 21 ]. Another alloy, namely a Pt containing metallic glass, was characterized by AFM indentation in UHV to quantitatively determine the hardness and deformation mechanisms by Arnaud Caron and Roland Bennewitz [ 22 ].…”
mentioning
confidence: 99%